2021
DOI: 10.1200/go.20.00596
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Capecitabine and Oxaliplatin Before Concurrent Capecitabine and Radiation in Locally Advanced Rectal Cancers: Experience of a Cancer Hospital in Pakistan

Abstract: PURPOSE To report the toxicity and pathologic response rates after adding neoadjuvant capecitabine and oxaliplatin (CAPOX) followed by concurrent radiation and capecitabine (CAPRT) and surgery in patients with locally advanced rectal cancer. MATERIALS AND METHODS We retrospectively analyzed medical records of 301 patients between January 2007 and December 2014. Patients were treated with four cycles of neoadjuvant chemotherapy comprising CAPOX, followed by radiotherapy at doses of 45-54 Gy in 25-30 fractions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A retrospective review 2016 reported a pathological complete response (pCR) rate of 12% for patients treated with this neoadjuvant approach [ 3 ]. However, a subsequent study in 2021, encompassing data from 2007 to 2014, indicated a notable improvement with a pCR rate of 52% and an acceptable toxicity profile [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective review 2016 reported a pathological complete response (pCR) rate of 12% for patients treated with this neoadjuvant approach [ 3 ]. However, a subsequent study in 2021, encompassing data from 2007 to 2014, indicated a notable improvement with a pCR rate of 52% and an acceptable toxicity profile [ 4 ].…”
Section: Introductionmentioning
confidence: 99%